Disease prevalence and severity assessment of Pratylenchus coffeae on an infected banana in Peninsular Malaysia - Paiko, A. S.; Tijjani, Ahmadu; Rashed, O.; Ahmad, Khairulmazmi; Sijam, Kamaruzaman; Alsultan, Wael (Mushroom Research Foundation, 2019)
Pratylenchus spp. cause considerable damage to the banana plant (Musa spp.) globally and although reported extensively in Malaysia, disease prevalence and infection severities have not been defined. The objective of this research, therefore, was to determine the prevalence of Pratylenchus coffeae and the extent of their damage on Musa spp. Of the 13 banana fields sampled, Pratylenchus nematodes were found in 76% of them. Proportions of root cortexes occupied by reddish brown lesion were significant in all the states. All the sampled areas exceeded the threshold limit, which is a 1% increment above 5% and is considered highly significant damage. The pathological reaction of P. coffeae against Pisang Berangan multiplications was observed after 12 weeks of growth in a glasshouse experiment. There were significant differences in vegetative growth within the various pathogen inoculation levels evaluated. Pisang Berangan showed a high level of susceptibility through the activity of polyphenol oxidase and peroxidase-induced resistance at all days after inoculation with P. coffeae compared to the control, except at week 12 where it declined or was non-significant from the control. Educating banana growers on the prevalence of this pathogenic parasite is therefore imperative for management decisions.